2016
DOI: 10.1037/pas0000291
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of psychometric and convergent validity for social anhedonia and social closeness.

Abstract: Social anhedonia is an important construct that describes individual differences in preferences for interacting in and experiencing pleasure from social interactions and has been a central construct in the schizotypy literature. The description of social anhedonia is very similar to that of social closeness from the personality literature. Yet, no published studies have directly compared associations between social anhedonia and social closeness with an array of other measures of anhedonia, personality, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The pattern of findings for personality/temperament were generally consistent with previous research as social anhedonia had stronger and more consistent associations with positive temperament as opposed to negative temperament or disinhibition (e.g., Gooding et al, 2017; Olino et al, 2016), which has been found in the adult literature. Indeed, the relationships between social anhedonia and negative temperament or disinhibition were greatly reduced when accounting for shared variance with positive temperament.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The pattern of findings for personality/temperament were generally consistent with previous research as social anhedonia had stronger and more consistent associations with positive temperament as opposed to negative temperament or disinhibition (e.g., Gooding et al, 2017; Olino et al, 2016), which has been found in the adult literature. Indeed, the relationships between social anhedonia and negative temperament or disinhibition were greatly reduced when accounting for shared variance with positive temperament.…”
Section: Discussionsupporting
confidence: 88%
“…A recent study of narrower facets of personality found that social anhedonia is negatively related to prosocial orientation, orderliness, goal striving, dependability, sociability, and activity (Gooding et al, 2017). Of various narrow facets, social anhedonia is most comparable to low social closeness (i.e., the propensity to engage with others, value and enjoy relationships, and be warm and affectionate) and both traits have a similar pattern of correlations within the personality hierarchy (Olino et al, 2016).…”
Section: Correlates Of Social Anhedoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, social anhedonia is not simply an extreme form of introversion, which is characterized by low positive emotion and a preference for solitude (10). Rather, it seems comparable to (low) social closeness captured in the personality literature (11). In short, social anhedonia is not merely a reflection of diminished social interest, but at its core entails a reduced positive appraisal of all aspects of interpersonal relationships.…”
Section: Introductionmentioning
confidence: 55%
“…In addition, these two constructs are not entirely separable, as one can certainly engage in pleasurable physical activities in a social setting (such as eating dinner with friends). This notion is supported by research showing strong correlations between measurements of social and physical anhedonia 51,52. Such aspects of anhedonia have been examined extensively in relation to schizophrenia 1.…”
Section: Methodologically and Theoretically Distinct Anhedoniasmentioning
confidence: 87%